Peningkatan Hasil Belajar Pai Dengan Menggunakan Metode Diskusi di Kelas IV SDN 16 Siparayo - Liasma, Liasma (EduSpirit : Jurnal Pendidikan Kolaboratif, 2024)
This study aims to improve student learning outcomes in the Islamic Religious Education (PAI) subject through the implementation of the discussion method. The research was conducted in two cycles, each consisting of planning, implementation, and evaluation stages. In Cycle I, the test results showed that only 40% of students achieved the Minimum Completeness Criteria (KKM), with an average score of 67.6. However, in Cycle II, there was significant improvement, with 73.3% of students achieving the KKM, and the average score increased to 78.4. Additionally, student participation in the learning process also improved, although challenges such as students’ lack of courage to ask questions were still observed. Overall, this study shows that the discussion method can enhance student learning outcomes and engagement in PAI learning